THE EFFECT OF ORGANIZATIONAL CULTURE AND JOB SATISFACTION TOWARDS THE PERFORMANCE OF EMPLOYEE WITH INFORMATION TECHNOLOGY AS MODERATING VARIABLE AT THE OFFICE OF DITLANTAS POLDA CENTRAL SULAWESI - Damopoli, Yantje Michael; Thahir, Harifuddin; Adda, Wahyuni (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This research aims to analyze the effect of organizational culture towards the performance of employee and the moderating role of information technology on the relationship between organizational culture and job satisfaction on the performance of employees of the Central Sulawesi Police Ditlantas office. This study applied quantitative descriptive analysis method and sampling technique through census sampling. The types of data used were quantitative and qualitative data, and the data sources were secondary data and primary data. Based on the results using the partial last square test, it shows that the organizational culture variable has an effect on employee performance. Furthermore, job satisfaction affects the employee performance and information technology variables mediate the relationship between organizational culture variables and job satisfaction on employee performance. Keywords: Organizational Culture, Job Satisfaction, Information Technology, Employee Performance